Purchase Intention in Luxury Food: The Role of Materialism, Social Comparison, and Bandwagon Effect - Andriana, Rinda; Handriana, Tanti; Dunstan, Crisphine Lyana (Universitas Airlangga, 2024)
Objective: This research aims to examine the influence of materialism, social comparison, and the bandwagon effect on purchase intention for luxury food products. Design/Methods/Approach: This study adopts a quantitative approach and employs Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using the SmartPLS 3 software. An online survey was conducted by distributing a questionnaire among 200 respondents. Findings: The results indicate a significant influence of materialism and the bandwagon effect on purchase intention. In contrast, no significant influence is found in the effect of social comparison on purchase intention. Originality/Value: This research contributes to the academic and marketing fields by providing insights into the role of materialism, social comparison, and the bandwagon effect on purchase intention, particularly in the luxury food product category. Practical/Policy implications: The findings of this study could be beneficial for marketers looking to promote their products, specifically in the luxury food category. Businesses could create distinctive products and promotions, such as offering limited edition menus or exclusive deals for VIP members, like access to secret menus or unique discounts. Marketers could utilize social media platforms by selecting influencers that align with the brand's luxury concept and appeal to the target audience. Viral campaigns also encourage audiences to compare themselves with social media celebrities, leading to a bandwagon effect and increasing brand loyalty.